Computer modeling of charge particle beam extraction and transport - Litovko, I.V.; Oks, E.M. (Вопросы атомной науки и техники, 2007)
The computer simulation of the extraction of high current charge particle beam from a plasma source and its transport has been used for investigation of the beam quality and its dependence from plasma parameters. The calculation has been made for different geometry extraction system as well as acceleration gap for purpose system optimization in attempt to generate the steady beam and to study the behavior and influence of different factors on beam parameters. The results indicate that the geometry extraction system, aperture shape and its diameter play an important role in beam formation process. Simulation shows that acceleration voltage and emission current essential influent on beam quality, intensity and beam divergence. The simulations are in a good agreement with experimental results and can provide the basis for optimizing of plasma source construction and its parameters for beam generation. Проведено чисельне моделювання формування пучків заряджених часток з плазмових джерел. Також було зроблено чисельні розрахунки транспортування пучка в дрейфовому просторі з урахуванням просторової компенсації заряду. На основі одержаних результатів можна здійснити оптимізацію конструкцій екстракціонної та прискорювальної систем плазмових джерел, а також оптимізувати параметри джерел та отримати пучки заряджених часток з заданими параметрами. Проведено численное моделирование формирования пучков заряженных частиц из плазменных источников, а также расчеты транспортировки пучка в дрейфовом пространстве с учетом пространственной компенсации заряда. На основе полученных данных можно оптимизировать конструкцию извлекающей и ускоряющей систем плазменных источников, а также оптимизировать параметры источников и получить пучки заряженных частиц с заданными параметрами.